1983
DOI: 10.1070/pu1983v026n12abeh004590
|View full text |Cite
|
Sign up to set email alerts
|

Multiparticle exciton-impurity complexes in semiconductors

Abstract: We have carried out a high-resolution x-ray scattering study of the first-order paraelectric (PE) to ferroelectric (FE) transition of BaTi03. Using a pulsed electric field to cross the PE-FE phase boundary, both the x-ray scattering and bulk polarisation associated with the equilibrium FE phase appear only after a well defined delay relative to the pulse onset. Subsequently, the polarisation evolves much more rapidly than the x-ray intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 8 publications
3
14
0
Order By: Relevance
“…However at a low excitation rate, emission from comparatively distant pairs dominates and the red shift is reduced. This effect has been previously observed in Si doped with donors and acceptors having similar activation energies 15 . The observed temperature-induced red shift is just the reverse of the well-known blue shift for DAP emission for shallow donors and acceptors 13 .…”
Section: Resultssupporting
confidence: 49%
“…However at a low excitation rate, emission from comparatively distant pairs dominates and the red shift is reduced. This effect has been previously observed in Si doped with donors and acceptors having similar activation energies 15 . The observed temperature-induced red shift is just the reverse of the well-known blue shift for DAP emission for shallow donors and acceptors 13 .…”
Section: Resultssupporting
confidence: 49%
“…The linear Zeeman splitting of the D 0 X [9] and A 0 X [10] has been studied and good agreement with the theory has been achieved. The QZE has also been observed for D 0 X [9] and A 0 X [10], but the relatively low magnetic fields used in the reported experimental studies left very high uncertainty in the value of the diamagnetic shifts.…”
Section: Introductionmentioning
confidence: 96%
“…In [15] the authors quoted the precision of the observed diamagnetic shift to be 4%, but they took all heavy and light hole D 0 X diamagnetic shifts to be the same. Data of the same field range as in [15] was treated separately in [9] and a more realistic precision of the order of 25% was reported. Our high magnetic field experiments allow us to measure the diamagnetic shifts with high precision (~1%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The observed spectra have been fit by calculating the transition energy of each of the sixty unresolved hyperfine components, and adding a line having a shape similar to the zero-field lineshape (but somewhat narrower) at that energy, with a relative intensity determined by D 0 X → D 0 selection rules, initial state thermalization, and the nuclear polarization. The known electron g-factor is used in the fits, and the D 0 X hole g-factors are adjustable parameters, together with the diamagnetic shifts [21] and the temperature dependence of the band gap energy, all of which are optimized across the spectra at various temperatures and B fields. An effective temperature, slightly higher than the nominal temperature, is obtained from matching the thermalization between the six main D 0 X transitions.…”
mentioning
confidence: 99%